Prevention of Internalising Problems in Younger Adolescents: The Development and Evaluation of a Universal Family Intervention - Drake-Brockman, Ruth Marguerite (Curtin University, 2023)
The family remains influential throughout adolescence, and has an important role to play in mental health promotion. The purpose of this research was to develop and evaluate a universal family intervention, aimed at enhancing protective factors and reducing risk factors associated with the development of anxiety and depression. The intervention was developed using qualitative methods, and complemented a previously validated school-based program. The efficacy of the intervention was evaluated in a large group randomised trial with socially disadvantaged communities.